MODIFIED BUTTERFLY ANTI-TENSION TAPE AS A PREVENTION OF HYPERTROPHIC SCAR IN FACIAL REGION MEASURED BY JAPANESE SCAR SCALE (JSS) - Gerardo Laksono; Herman YL Wihastyoko; Paul L Tahalele (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Introduction: Abnormal scar remains an unsolved problem in some countries marked by an increase of prevalence of abnormal scar in the last 2 to 3 decades. Prevention of abnormal scar is essential but there aren't many therapy modalities as prevention followed by affordable prices to all society groups for abnormal scar.Purpose: to determine the effect of anti-tension tape in the shape of a butterfly as a hypertrophic scar prevention measured by Japanese Scar Scale (JSS). Method: This is an analytic study with an observational study design and a cohort study method. Total sample used in this study is 80, divided into 2 groups contains 40 patients who got anti tension tape application and patient who didn't. The anti tension tape was used for 3 months. Chi-Square was used as a statistical analysis in this study. Results: From 40 samples in anti-tension tape application group, 33 patients have normal scar, 7 patients have hypertrophic scar. From 40 patients in control group, 11 patients have normal scar and 29 patients have hypertrophic scar. Statistical analysis using chi-square showed p=0.000. Conclusion: Modified butterfly anti-tension tape can be used as on therapy modality as a prevention of Hypertrophic scar measured by Japanese Scar Scale.